PHYSICAL AND FUNCTIONAL PROPERTIES OF FERMENTED CASSAVA STARCH USING Lactobacillus plantarum - Suseno, Rahayu; Ulyarti, Ulyarti; Sari, Dian Wulan; Gusriani, Ika; Rahmayani, Irma; Mursyid, Mursyid (Jurnal Teknologi Pertanian, 2026)
Lactobacillus plantarum is one of the lactic acid bacteria that dominates during the natural fermentation of cassava. It can also be used as a single starter culture for cassava fermentation, producing modified cassava flour with improved physical and functional properties. As the main component of cassava flour, starch is expected to contribute to the changes that occur during fermentation. However, limited information is available regarding the effect of L. plantarum fermentation on cassava starch.  This study aimed to determine the effects of inoculum concentration and fermentation time on the physical and functional properties of cassava starch fermented using L. plantarum. The experiment was arranged in a randomized complete factorial design with two factors: inoculum concentration (1, 2, and 3% v/v) and fermentation time (24, 48, and 64 hours).  Scanning electron microscopy (SEM) images of the starch samples showed no changes in granule morphology. Statistical analysis demonstrated that neither inoculum concentration nor fermentation time significantly affected bulk density, water absorption capacity (WAC), oil absorption capacity (OAC), swelling power, or solubility at 65, 70, 75, 80, 90, and 95 °C. However, fermentation time significantly affected starch solubility at 85 °C (p < 0.05). These results indicate that starch may not be the only component influencing the physical and functional properties of fermented cassava starch.